الصراع الداخلي على الشخصية الرئيسية في القصة القصيرة الملاك الأعرج لمنى مرشود - syarifah syarifah (EL- Hayah, 2024)
This research examines the psychological aspects in the short story "The Lame Angel". This research is a qualitative descriptive study using Kurt Lewin's literary psychology approach. The data collection techniques used in this research were library techniques, reading and note-taking. In this research, he began to use Kurt Lewin's theory to identify interactions that occurred between the main character and other characters which led to conflict. The results of this research show that the author mentions internal conflict in the short story "The Lame Angel" by Mona Marchoud. By using Kurt Lewin's psychological studies, two things can be concluded. First, getting closer indicates a form of internal conflict, happiness, and anxiety. Approach-distancing conflict takes the form of disappointment, fear and anger, while Approach-distancing conflict takes the form of disappointment, annoyance and anxiety. Second: The response to resolving internal conflict in the short story is divided into three parts, namely 1) anxiety, 2) bargaining, 3) choice/rejection. These three actions carried out by the main character occur until the main character understands himself and is able to accept the current situation.